Odpowiedzi

2010-01-19T20:54:47+01:00
A)(x-2)-(2-x)=x-2-2+x=2x-4=2(x-2)

b) (a+b)+(2a-b)-(a-2b)=
a+b+2a-b-a+2b=2a+2b=2(a+b)

c) (3x-y+1)-(x+y)+(y-x)
3x-y+1-x-y+y-x=x-y+1

d) -(2a²-3ab)-(2b-3a²)+(-ab-b)
-2a²+3ab-2b+3a²-ab-b=a²+2ab-3b
2010-01-19T20:58:54+01:00
A)
(x-2)-(2-x)= x -2 -2-x= 2(x-2)

b)
(a+b)+(2a-b)-(a-2b)=a+b+2a-b-a+2b=2a+2b

c)
(3x-y+1)-(x+y)+(y-x) =3x-y+1-x-y+y-x=x-2y+1

d)
-(2a²-3ab)-(2b-3a²)+(-ab-b)=
=-2a +3b - 2b + 3a² -ab -b=
=3a²-2a- ab+3b=
=a(3a-2)+b(3-a)

Nie jestem pewien czy to jest dobrze